Upaya Mendorong Masyarakat Mengenai Pentingnya Kepatuhan Perpajakan di Kalangan UMKM Desa Caturharjo - Kuni Naila’L Muna; Hasim As’ari (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community service process aims to increase community knowledge and awareness regarding Final Income Tax for MSMEs. The partners of this activity are fashion businesses and grocery stores in Caturharjo village, Sleman District, Sleman Regency. The type of this activity is carried out in discussions, case studies, simulations, training, and assessments with a direct meeting method. This service was carried out for 5 meetings which were held on October 6, 13, 20, 26, 27, and November 3, 2024. This process is carried out in stages by coming directly to the partner's place. The results of this community service provide results to target partners in the form of increased understanding of taxation, Final Income Tax for MSMEs, calculation of Final Income Tax, and the process of making NPWP.